2007
DOI: 10.1063/1.2727460
|View full text |Cite
|
Sign up to set email alerts
|

Total dissociative electron attachment cross sections of selected amino acids

Abstract: Total dissociative electron attachment cross sections are presented for the amino acids, glycine, alanine, proline, phenylalanine, and tryptophan, at energies below the first ionization energy. Cross section magnitudes were determined by observation of positive ion production and normalization to ionization cross sections calculated using the binary-encounter-Bethe method. The prominent 1.2 eV feature in the cross sections of the amino acids and the closely related HCOOH molecule is widely attributed to the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 42 publications
(53 reference statements)
3
47
1
Order By: Relevance
“…H-mode is known to have a higher ion temperature than E-mode [12,13,15] and this is a considerable source of heating in plasmas. Additionally, the higher electron density and electron energy distribution function (EEDF) at lower values, found in H-mode, can also lead to dissociative electron attachment (DEA) on sample surface, which could also increase heating by bond dissociation [26].…”
Section: Resultsmentioning
confidence: 99%
“…H-mode is known to have a higher ion temperature than E-mode [12,13,15] and this is a considerable source of heating in plasmas. Additionally, the higher electron density and electron energy distribution function (EEDF) at lower values, found in H-mode, can also lead to dissociative electron attachment (DEA) on sample surface, which could also increase heating by bond dissociation [26].…”
Section: Resultsmentioning
confidence: 99%
“…The lower 2.7 and 3.5 eV resonance energy are associated with the π * unoccupied orbital of the carboxyl group. The broad resonances at 9.8 and 8.6 eV cannot be easily assigned to a specific process, but it has been suggested [71] that it could arise from a core-excited states or σ * unoccupied orbital of OH group [50].…”
Section: Discussionmentioning
confidence: 99%
“…The most important positive fragments obtained were ions with m/Z of 74, 44 and 28 and appearance energies of 10.74, 9.10 and 10.85 eV, respectively. Total dissociative electron attachment cross sections have been measured for the amino acids glycine, alanine, proline, phenylalanine, and tryptophan, at energies below the first ionization energy by Scheer et al [50].…”
Section: Introductionmentioning
confidence: 99%
“…It has been already found that DNA damage by LEE, involves electron capture by a particular DNA components followed by the decay into dissociative electron attachment (DEA) and other dissociative channels [12]. Moreover, the common feature in the DEA cross sections of formic acid and some selected amino acids was attributed to the attachment into the -COOH π* orbital, but very recently also the evidence of direct attachment to the lowest σ* orbital was reported [13]. There are many recent experimental studies concerning DEA to the monomeric [14,15,16,17,18,19] and cluster [20] forms of formic acid in the gas phase.…”
Section: Introductionmentioning
confidence: 99%